Pericytes take up and degrade α-synuclein but succumb to apoptosis under cellular stress - Taylor J. Stevenson; Rebecca H. Johnson; Jimmy Savistchenko; Justin Rustenhoven; Zoe Woolf; Leon C. D. Smyth; Helen C. Murray; Richard L. M. Faull; Jason Correia; Patrick Schweder; Peter Heppner; Clinton Turner; et al. (Scientific Reports, 2022)
Abstract Parkinson’s disease (PD) is characterised by the progressive loss of midbrain dopaminergic neurons and the presence of aggregated α-synuclein (α-syn). Pericytes and microglia, two non-neuronal cells contain α-syn in the human brain, however, their role in disease processes is poorly understood. Pericytes, found surrounding the capillaries in the brain are important for maintaining the blood–brain barrier, controlling blood flow and mediating inflammation. In this study, primary human brain pericytes and microglia were exposed to two different α-synuclein aggregates. Inflammatory responses were assessed using immunocytochemistry, cytometric bead arrays and proteome profiler cytokine array kits. Fixed flow cytometry was used to investigate the uptake and subsequent degradation of α-syn in pericytes. We found that the two α-syn aggregates are devoid of inflammatory and cytotoxic actions on human brain derived pericytes and microglia. Although α-syn did not induce an inflammatory response, pericytes efficiently take up and degrade α-syn through the lysosomal pathway but not the ubiquitin–proteasome system. Furthermore, when pericytes were exposed the ubiquitin proteasome inhibitor—MG132 and α-syn aggregates, there was profound cytotoxicity through the production of reactive oxygen species resulting in apoptosis. These results suggest that the observed accumulation of α-syn in pericytes in human PD brains likely plays a role in PD pathogenesis, perhaps by causing cerebrovascular instability, under conditions of cellular stress.